2015
DOI: 10.1620/tjem.235.161
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-141 Is a Biomarker for Progression of Squamous Cell Carcinoma and Adenocarcinoma of the Lung: Clinical Analysis of 125 Patients

Abstract: Lung cancer is the most common malignant tumor worldwide. MicroRNA has become an ideal biomarker for cancer diagnosis, prognosis and therapy. The relationship between microRNA-141 and non-small cell lung cancer (NSCLC) is contradictory. Thus, in current study, we aimed to investigate the level of microRNA-141 in NSCLC tissues and to evaluate its potential clinical value. This study enrolled 125 NSCLC patients (75 males and 50 females) with a median age of 61 years (range, 23-90 years). NSCLC patients included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…This miRNA was a powerful indicator for predicting the chemosensitivity of lung adenocarcinoma patients to docetaxel-based chemotherapy regimen. Zhang et al [32] analyzed the clinical potential of miR-141 and found that this miRNAs was positively correlated with the tumor size, lymph NOGe metastasis, and TNM stage of lung adenocarcinomas. Meanwhile, Liu et al [34] screened that the upregulation of plasma exosomal miRNAs miR-23b-3p, miR-10b-5p and miR-21-5p was strongly connected with the poor overall survival of lung adenocarcinoma patients.…”
Section: Resultsmentioning
confidence: 99%
“…This miRNA was a powerful indicator for predicting the chemosensitivity of lung adenocarcinoma patients to docetaxel-based chemotherapy regimen. Zhang et al [32] analyzed the clinical potential of miR-141 and found that this miRNAs was positively correlated with the tumor size, lymph NOGe metastasis, and TNM stage of lung adenocarcinomas. Meanwhile, Liu et al [34] screened that the upregulation of plasma exosomal miRNAs miR-23b-3p, miR-10b-5p and miR-21-5p was strongly connected with the poor overall survival of lung adenocarcinoma patients.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-141 can also be a potential biomarker for the molecular diagnosis and risk stratification in NSCLC. MiR-141 was reported to be upregulated in NSCLC tissues compared with the corresponding normal ones by several independent studies [62,84,144]. This excessive expression of miR-141 was further proved to be associated with the larger tumor size, lymph node metastasis and advanced stage in NSCLC patients.…”
Section: Mir-141 In Cancer Diagnosis and Prognosismentioning
confidence: 94%
“…Previous studies have also identified overexpression of miRNA-141 and miRNA-217 in tumor tissue [8]. Interestingly, upregulation of miRNA-217 was associated with an advanced status of NSCLC.…”
Section: Discussionmentioning
confidence: 75%
“…miRNA-34a regulates tumor cell apoptosis, and one very promising approach in NSCLC therapy involves the restoration of its correct function [7]. miRNA-141 is known as a predictive marker in NSCLC as it regulates sensitivity to cisplatin [8]. Apart from its prognostic value, miRNA-141 overexpression correlates with the more advanced stage of NSCLC and has potential as a diagnostic molecular biomarker.…”
Section: Introductionmentioning
confidence: 99%